Organisational behaviour in the public sector : a critical introduction - Fenwick, John (Professor of Public management) (Emerald Publishing Limited, 2021)
This book adopts a highly critical approach to the ways in which organisations have been analysed by orthodox theories and offers instead a perspective on elements of organisational behaviour including leadership and its failures, structures, cultures, bullying and the denial of individual voice, firmly rooted in the critical understanding of power and control. Professor Fenwick draws from international examples of practice and finds grounds for optimism in the distinctive positive values of the public sector organisation. This book is an invaluable source for those with an interest in organisational behaviour in the public sector, designed for many audiences including students embarking upon study of how such organisations work, researchers who wish to assess aspects of the topic in greater depth, or readers with a practical interest or involvement with the organisations in question.
Includes index.
Keywords: Public administration -- Management.; Organizational behavior.; Political Science -- Public Affairs & Administration.; Public administration.; elektronické knihy; electronic books